Analisis Penerimaan Guru Terhadap Penggunaan Aplikasi E-Raport Menggunakan Metode Technology Acceptance Model di SMK Negeri 2 Padang - Wahyuni, Rada Puspa; Irsyadunas, Irsyadunas; Novita, Rini (Universitas Labuhanbatu, 2024)
In the era of globalization as it is today, Information and communication technology is defined as the development of an important element and has a great influence on humans.Computers or gadgets become data processing devices and communication media that are very important in a job. No exception in the world of education that also uses these technological advances in the learning process, such as in schools and colleges. The use of e-report cards in schools still has its own challenges, especially in terms of acceptance and use by teachers. There are still various factors that can affect the acceptance and use of e-report card the application of Information Systems Technology in the field of Education. E-report card is one of the implementation of the application of Information Systems Technology in the field of education that serves in making the results of Student Assessment Reports. E-report cards provide benefits for teachers to process students ' academic and non-academic grades, and assist schools in preparing assessment reports in accordance with existing assessment guidelines. E- report information system is used to process the attitude value, knowledge value, and skill value that teachers put into the final grades of students. The results of observations and interviews that have been conducted with E-report card admin, subject teachers and homeroom teachers of SMK Negeri 2 Padang. Researchers found several facts that the difficulties and problems in using the E-Report Card system. It can be seen that there are teachers who have difficulty using E-report cards because the network is unstable, there are still teachers who do not understand the features of the E-Report Card application so that the difficulty when using it, there are still teachers who have difficulty when using the E-Report Card system, because the time when filling in the value is also limited, if there is a delay the teacher automatically cannot perform the assessment process to the E-Report Card Application System.